2009
DOI: 10.1093/fampra/cmp018
|View full text |Cite
|
Sign up to set email alerts
|

Foot problems in children presented to the family physician: a comparison between 1987 and 2001

Abstract: Total incidence rate of musculoskeletal foot problems seen by the FP has decreased substantially, between 1987 and 2001.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…In addition, the prevalence of overweight and obesity peaks around this age and is higher in women [31], and there is some evidence that obesity may be a risk factor for foot pain [8–10]. The higher annual consultation prevalence of males aged <14 years may be due to a higher prevalence of conditions such as flat feet, heel pain, trauma and congenital deformities compared with females [18, 20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the prevalence of overweight and obesity peaks around this age and is higher in women [31], and there is some evidence that obesity may be a risk factor for foot pain [8–10]. The higher annual consultation prevalence of males aged <14 years may be due to a higher prevalence of conditions such as flat feet, heel pain, trauma and congenital deformities compared with females [18, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…While there has been some examination of consultation patterns for foot surgery [17, 18], relatively little is known about the characteristics of foot problems presenting to GPs. To the best of our knowledge, the only detailed assessments of primary care consultations for foot problems have been conducted in the Netherlands, one of which specifically focused on children [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Flexible flat foot (also known as pes planus or planovalgus) in children, when there is the appearance of a lowered medial longitudinal arch, with or without rearfoot eversion [ 1 ] is one of the most frequently reported reasons to seek orthopaedic opinion [ 2 ]. Yet, in typically developing children, normative data indicates ‘flat’ is normal for children up to eight years of age [ 3 ], due to age appropriate osseous and ligamentous laxity, increased adipose tissue and immature neuromuscular control [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Riddiford-Harland et al [20] and Dowling et al [21] demonstrated that medial longitudinal arches of the foot of overweight/obese children were flatter and Chippaux-Smirak Index of their footprints were higher than in normal weight children. Krul et al [22] reported that lower limb musculoskeletal complaints and problems were more frequent in overweight/obese children compared to normal weight children seen in primary care clinics.…”
Section: Discussionmentioning
confidence: 99%